Towards Precritical Medical Therapy of the Abdominal Aortic Aneurysm - Lucia Musumeci; Wolf Eilenberg; Joël Pincemail; Koichi Yoshimura; Natzi Sakalihasan (Biomedicines, 2022)
Pharmacotherapy for abdominal aortic aneurysm (AAA) can be useful for prevention, especially in people at higher risk, for slowing down AAA progression, as well as for post-surgery adjuvant treatment. Our review focuses on novel pharmacotherapy approaches targeted towards slowing down progression of AAA, known also as secondary prevention therapy. Guidelines for AAA are not specific to slow down the expansion rate of an abdominal aortic aneurysm, and therefore no medical therapy is recommended. New ideas are urgently needed to develop a novel medical therapy. We are hopeful that in the future, pharmacologic treatment will play a key role in the prevention and treatment of AAA.